Ethyl 4-(3-hydroxyphenyl)-2,7,7-trimethyl-5-oxo-1,4,5,6,7,8-hexahydroquinoline-3-carboxylate - P. Mookiah; K. Rajesh; T. Narasimhamurthy; V. Vijayakumar; N. Srinivasan (Acta Crystallographica Section E, 2009)
In the molecular structure of the title compound, C21H25NO4, the dihydropyridine ring adopts a flattened boat conformation while the cyclohexenone ring is in an envelope conformation. In the crystal structure, molecules are linked into a two-dimensional network parallel to (10overline{1}) by N—H...O and O—H...O hydrogen bonds. The network is generated by R44(30) and R44(34) graph-set motifs.